2008
DOI: 10.1203/pdr.0b013e3181761859
|View full text |Cite
|
Sign up to set email alerts
|

Increased Elastic Tissue Defect Formation in the Growth Restricted Brown Norway Rat: A Potential Link Between In Utero Condition and Cardiovascular Disease

Abstract: Low birth weight for gestational age has been epidemiologically linked to cardiovascular mortality and morbidity in adult life. This study aimed to determine whether in utero growth restriction influences an early feature of atherosclerotic pathology; disruption of the aortic internal elastic lamina (IEL) in the adult Brown Norway (BN) rat. In utero growth restriction was induced by bilateral uterine artery ligation on day 18 of gestation, thereby decreasing newborn BN pup weight by approximately 14%. Restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although increased elastin deposition may be counterintuitive in relation to increased stiffening, Arribas and colleagues (2008) showed that an increased deposition of abnormally organized elastin is associated with artery wall stiffening in blood vessels of spontaneous hypertensive rats even before the development of hypertension. Furthermore, our group has also shown that uteroplacental insufficiency was associated with increased internal elastic lamina defects in the aorta of male and female offspring (Pascoe et al 2008). Thus, if elastin is disorganized, these alterations in elastin may contribute to the vascular stiffness and narrowing of uterine arteries in Restricted females.…”
Section: Discussionmentioning
confidence: 88%
“…Although increased elastin deposition may be counterintuitive in relation to increased stiffening, Arribas and colleagues (2008) showed that an increased deposition of abnormally organized elastin is associated with artery wall stiffening in blood vessels of spontaneous hypertensive rats even before the development of hypertension. Furthermore, our group has also shown that uteroplacental insufficiency was associated with increased internal elastic lamina defects in the aorta of male and female offspring (Pascoe et al 2008). Thus, if elastin is disorganized, these alterations in elastin may contribute to the vascular stiffness and narrowing of uterine arteries in Restricted females.…”
Section: Discussionmentioning
confidence: 88%
“…In sheep, aortic vascular remodeling was associated with increased collagen (100) and reduced elastin content that was vascular bed specific as no changes were observed in the superior mesenteric artery (401). An increased occurrence of aortic internal elastic lamina defects was also observed in offspring of bilateral uterine artery ligation rats (299). Vascular remodeling has been observed in the pulmonary arteries, where maternal nutrient restriction led to increased smooth muscle thickness following acute (240) or chronic (375,445) exposure of the offspring to hypoxia.…”
Section: Vascular Remodelingmentioning
confidence: 95%
“…An increased number of smooth muscle cells, however, might not necessarily reflect improved constrictor capacity if the components of the cell were disrupted or malformed. Indeed, some of the vascular remodeling work has shown that an increased number of defects were observed in the elastic lamina layers (299). Furthermore, vascular stiffness was shown to be increased as a result of increased collagen content, and this could hinder the flexibility of the vessel both in terms of vasodilation and vasoconstriction; therefore, both increased and decreased responses to KCl could be equally indicative of vascular dysfunction following a compromised pregnancy.…”
Section: Vasoconstrictor Mechanismsmentioning
confidence: 99%
“…These findings are more characteristic of atherogenic vascular remodelling rather than the vascular structural matrix changes associated with abnormal arterial stiffness [84]. Other studies of rat RUPP offspring have also identified an increased propensity to develop arterial internal elastic lamina lesions, an early atherosclerotic process, when studied at 8 and 16 weeks of age [64]. …”
Section: Mechanism Of Long-term Programing? the Cardiovascular Systemmentioning
confidence: 99%